2020
DOI: 10.1088/2057-1976/aba880
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel 3D printed plastic scintillation dosimeters

Abstract: We propose a new methodology for the fabrication and evaluation of scintillating detector elements using a consumer grade fusion deposition modeling (FDM) 3D printer. In this study we performed a comprehensive investigation into both the effects of the 3D printing process on the scintillation light output of 3D printed plastic scintillation dosimeters (PSDs) and their associated dosimetric properties. Fabrication properties including print variability, layer thickness, anisotropy and extrusion temperature were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…For comparison, our previous work also showed an average difference of 2.3% and a maximum of 4.0% between scintillators printed with identical print parameters. 1 However, identically designed arrays printed using the same print parameters demonstrate a similar distribution of element sensitivities. This suggests that there is potential for improvements to the printing process.…”
Section: Dual-materials 3d Printing Of Scintillator Arraysmentioning
confidence: 96%
See 4 more Smart Citations
“…For comparison, our previous work also showed an average difference of 2.3% and a maximum of 4.0% between scintillators printed with identical print parameters. 1 However, identically designed arrays printed using the same print parameters demonstrate a similar distribution of element sensitivities. This suggests that there is potential for improvements to the printing process.…”
Section: Dual-materials 3d Printing Of Scintillator Arraysmentioning
confidence: 96%
“…11 Recently our group has published the first example of characterizing an FDM 3D printed scintillator produced using a commercially available scintillating fiber. 1 We demonstrated that these 3D printed scintillators shared many desirable properties with their commercial counterparts such as dose linearity, dose rate independence, energy independence in the MV range, repeatability, and stability. This work builds on the previous publication by integrating techniques learned from 3D printing individual scintillating elements into the production of multi-element scintillating arrays and their wireless measurement using an sCMOS camera.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations